(untitled) (Theatrum historiae, 2018)
The Anabaptist physicians, barbersurgeons and midwives played an important part in the medicine of the 16th and 17th century. They were required by both the Bohemian and Moravian nobility, regardless of their theological radicalism, for their skilfulness and for the increasing demand for physicians in the 16th century. In consequence of their longterm absence in the Anabaptist communities, caused by the travels to the noble patients, the physicians and barbersurgeons were predisposed to be independent and reluctant to submit to the order prevailing in the Anabaptist communities. Still, they belonged to the most prominent members of the fellowship. The Anabaptist midwives were, similarly to the physicians and barbersurgeons, demanded by the Moravian nobility, but for the lack of sources, the substance of the Anabaptist midwifery remains unknown.